PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS PEGAWAI PADA KANTOR BKPSDM KOTA PALOPO - Pukan, Yohana Nelsi; Parwata, Dewa Made; Anggraini, Devi; Rasni, Rasni; Khaerana, Khaerana (Lembaga Pengembangan Kinerja Dosen, 2023)
Work productivity is needed to achieve the goals that have been set. Work productivity is often interpreted as an attitude that absolutely holds the view that today's work methods must be better than yesterday's work methods in that the results that can be achieved tomorrow must be more or higher in quality than the results achieved today.This research will be carried out at the Office of the Personnel and Human Resources Development Agency in Palopo City, which is located on Jl. Andi Djemma No. 66 Tompotikka Village, Wara District, Palopo City. The Influence of Training on Employee Work Productivity at the BKPSDM Office in Palopo City. This study aims to describe the Effect of Training on Employee Work Productivity at the BKPSDM Office in Palopo City. The type of research used in this study is a qualitative method. Data collection techniques using a questionnaire as many as 24 respondents. The data analysis technique used is descriptive analysis technique, validity test, reliability test, and linear regression analysis. The sampling method used is saturated samples. Based on sports data, the result is that training has a significant effect on work productivity.